Performance improvement of thermoelectric generator by drooping the cool side temperature with thermacool 0.3M coating. (November 2022) - Ramkumar, Alajingi; Ramakrishnan, Marimuthu
Abstract: The hot side of Thermoelectric generator (TEG) receives heat from the heat source. Meanwhile, the output power and voltage depend on the temperature gradient between the hot and cold junction. Drooping the cold side temperature of TEG can increase the temperature gradient between its junction and subsequently the performance of the device. The conventional heatsinks used for heat dissipation and temperature drooping are at least twice as bulky as TEGs. Hence as an alternative, this work proposes coating of acrylic polyurethane-based heat reflective coating (Thermacool 0.3M) of 120 μm on cold side of TEG for drooping cold side temperature. To evaluate the performance of proposed system TEG (SP1848-27145) is tested in controlled temperature environment, Initially with heat sink model and later with thermacool 0.3M coating. A mathematical model has also derived for validation. The retardation in temperature of both model's cold side from 90 °C with respect to time are recorded. It is observed that after 4-minute of natural convection cooling the thermacool 0.3M coated model cool side temperature is 34 °C compared with 39 °C cool side heat sink attached model. There is a significant improvement in power, efficiency and figure of merit parameters of 0.18W, 3.8% and 0.04 respectively.